(untitled) (Journal of Bio-Science, 2026)
Petroleum ether, chloroform (CHCl3) and methanol (CH3OH) extracts of the flowers and leaves of Caesalpinia pulcherrima (L.) were evaluated for their larvicidal activity against Culex quinquefasciatus Say and their repellent activity against three stored grain pests: Tribolium castaneum (Hbst.), Sitophilus oryzae (L.) and Callosobruchus chinensis (L.). The LC50 values ​​of the petroleum ether and CHCl3 extracts of the flowers were 119.80, 37.34, 25.06, 17.12, and 10.36 ppm and 101.04, 76.67, 66.67, 58.24, and 51.82 ppm, respectively, after 24, 30, 36, 42, and 48 h of exposure. The CHCl3 leaf extract showed LC50 values ​​of 361.21, 321.10, 245.41, 207.09, and 203.19 ppm after 24, 30, 36, 42, and 48 h of exposure, respectively. Depending on the intensity of larvicidal activity on the mosquito, the extracts can be classified in descending order as follows: petroleum ether (flower) >CHCl3 (flower) >CHCl3 (leaf). Extracts of flowers with petroleum ether demonstrated a highly significant repellent effect against adult T. castaneum (p<0.01), extracts of leaves with CHCl3 and CH3OH showed a moderately significant repulsion against adult T. castaneum (p<0.05), and extracts of leaves with petroleum ether also showed a moderately significant repulsion against adult S. oryzae (p<0.05). J. Bio-Sci. 33(2): 77-86, 2025